STUDY ON THE LOAD DISTRIBUTION BY A CHARGE CONTROLLER OF A PASSIVE SOLAR GREENHOUSE - Yaacob, Mohd Rusdy; Yusuf Lada, Musa (2012)
This paper presents a study on the load distribution in a passive solar greenhouse through a self-developed charge controller. The study has been conducted in which the controller was being tested with 12 V 1.2Ah battery to measure the battery voltages over time in different load’s conditions. The battery voltage measurement was taken from a digital panel display consists of IC TC7107 and seven segments display which were connected to the SPC3 charge controller. This controller consists of both charging and low voltage disconnect circuits and is able to work with solar charged 12V DC system. The results obtained are the values of the battery voltage connected with no load, fan, motor and both fan and motor. These data were then converted into graph that illustrates the behavior of load distribution in a passive solar greenhouse.